Unlocking Loyalty: The Power of Local Culture in Bali Tourism - I Ketut Putra Suarthana; I Made Bayu Wisnawa; Ni Luh Putu Agustini Karta; Karunavani Sarukunaselan (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
This article examines the influence of local culture on tourist loyalty, focusing on a case study in Bali, Indonesia. Through a quantitative approach, this study uses structural equation modelling (SEM) with smart partial least squares (PLS) to analyse data from a survey involving 276 tourists. This study identifies and measures the direct impact of two independent variables, namely local ‘cultural richness’, and ‘cultural interaction’, on destination loyalty, with ‘tourist satisfaction’ as the mediating variable and ‘previous travel experience’ as the moderating variable. The results show that local cultural richness and cultural interaction have a significant influence on tourist satisfaction, which in turn affects destination loyalty. Nonetheless, previous travel experience has proven not to moderate the relationship between tourist satisfaction towards destination loyalty (? = -0.021). These findings provide valuable insights for destination managers and policymakers in developing marketing strategies that focus on local culture to increase tourist loyalty.